Rational Choice in Abortion: A Case Study of Urban Children - Larasati, Yuniar Galuh; Fernando, Henky; Morin, Leanne (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2024)
Abortion by children is not only an impulsive act but also a rational choice, which is crucial to explain and evaluate. However, this phenomenon has been overlooked in previous scholarly discussions. In addition, responding to the gaps in previous studies, this study aims to explain the forms, factors, and implications of abortion by children in urban areas as a rational choice. Using a qualitative descriptive approach based on case studies, this study reveals three important findings. First, the practice of abortion by children in urban areas is carried out in various ways, both medical and non-medical. Second, abortions performed by children in urban areas are often influenced by social pressures such as their partners, parents, and the community. Third, abortion among children in urban areas has long-lasting implications for their physical, mental, and social well-being. Based on these findings, this study also recommends the importance of future studies that conduct intensive interviews to reveal the motives and modes of children in having more reflective abortions.